Cryptotendipes Lenz from Manitoba, Canada, with keys to known immatures of the genus (Diptera: Chironomidae) - Sæther, Ole A. (Zootaxa, 2010)
Cryptotendipes tuberosus sp. n. from Southern Indian Lake, Manitoba, Canada, is described in all stages and both sexes. Five additional species of Cryptotendipes Kieffer are recorded from Lake Winnipeg, and two from South Indian Lake. C. ariel (Sublette) is shown to be a senior synonym of C. darbyi (Sublette). The pupae and larvae of C. emorsus (Townes), C. casuarius (Townes), C. darbyi and C. pseudotener (Goetghebuer) are described or redescribed. The female of C. emorsus is described and additional information given on other male and female imagines. Keys are given to known pupae and larvae of Cryptotendipes. The distribution of Cryptotendipes in Lake Winnipeg is mapped and discussed. The separation of larval instars is shown approximately to follow Dyar’s rule.